Facies Architecture And Depositional Marine Systems of the Yamama Formation in Selected Wells, Southern Iraq - Mohsin, Shatha A.; Mohammed, Abbas H.; Alnajm, Fahad M. (Iraqi Journal of Science, 2023)
The Yamama Formation is characterized by a wide geographic extension of southern Iraq. Microfacies analysis of this formation was studied in six wells distributed in six fields: Fayhaa, Sindbad, Siba, Zubair, Ratawi and West Qurna. This research aims to determine paleoenvironments by diagnosing biofacies and lithofacies. Miscellaneous marine fauna of foraminifera and calcareous algae, mainly green algae (dasycladacean.) and skeletal bioclasts from gastropods, pelecypods, bryozoans, sponge spicules, and echinoderms were found. Petrographic studies and well logs interpretations led to the identification of five main Microfacies ( Mudstone, Wackestone, Packestone, Grainestone and Rudstone and twelve submicrofacies (Foraminiferal-Lime mudstone submicrofacies, Argillaceous Lime Mudstone submicrofacies, Planktonic foraminiferal – Lime Wackestone submicrofacies, piculites/ Calcisphers – Lime Wackstone submicrofacies, Benthonic Foraminiferal -Lime wackestone/packestone submicrofacies, Algal (desycladecan) Lime wackestone submicrofacies, Algal-Lime packestone submicrofacies, Bioclastic/ Algal-Lime packestone submicrofacies, Algal/ Foraminiferal- Algal -Lime packstone submicrofacies, Peloidal poorly sorted grainstone with bioclasts submicrofacies, Intraclastic grainstone submicrofacies, Pesudo oolitic-Lithocodium aggregatum grainstone submicrofacies and finally Peloidal-intraclastic, and bioclastic grainstone submicrofacies). Microfacies are deposited in the lagoon, shoal, rudist biostrome and open marine gradient to middle and outer ramp environments. Vertical changes in microfacies with depth were reflected by lateral changes in marine depositional systems and the thickness of the formation. Shoal environments’ microfacies are characterized by high thickness, while low thickness characterizes the open marine microfacies. The Yamama Formation was deposited on the low-angle homoclinic carbonate ramp, mainly in the inner and middle ramp, with outer ramp conditions in some parts of the formation.